Suitability study of using thermoplastic starch coating material for Harum Manis (MA128) mango in post harvest management / Yazid Mohd Esa, Sharizal Hasan and Mohd Lias Kamal - Mohd Esa, Yazid; Hasan, Sharizal; Kamal, Mohd Lias (Universiti Teknologi MARA, Perlis, 2006)
In this study, plasticized starch with glycerol was used to coat Harum Manis (HM) mango fruits and observed for basal end rot (BER) incidences caused by the common pathogen Botryodiplodia theobromae Pat. and the possible effect of coating on the sugar content of the mangoes. The starch coating of mango fruits delayed the onset of BER infection by at least four days after incubation period. Coating without incubation gave superior results compared to coating after incubation. Both methods however only showed BER symptoms on day seven after opening of closure after incubation. All the fruits manifested symptoms of BER on day 11 in all the treatments. Coating HM mangoes with the starch formulation did not give any significant effect in the rate to reach maximum sugar content.